Speaking Anxiety and its Influences on Students Performances in English Class at STMIK AMIK Jayanusa - Allen Christy Jufri (Jurnal Pendidikan dan Konseling (JPDK), 2022)
In STMIK AMIK Jayanusa Padang was found that semester IV students had a problem in speaking anxiety in English class. The students still have difficulties comprehend English concept and difficulties in expressing their ideas in speaking. There are some factors which seems to cause the difficulty. Anxiety becomena majorzfactor thatpcould influencehtheir abilitymin languageblearning. In speaking class, student tend to be silent if they are asked by their lecture. Many times they keep silence even if they understand the question and could actually answer the question from their lecture. The students unable towmanage theirmemotion includingvnervousness, lackmof self confidences, shyness and the student fear to make mistake when they speak in front of the class. The sources of the data were the student of information system of STMIK AMIK Jayanusa Padang who are in the fourth semester that consist of 50 students. There were 12 students as a sample or 25 % for doing the questionnaire. There are three indicators for anxiety, they are communicationmapprehension, fearbof negativegevaluation and testlanxiety.